PROSEDUR PEMBERIAN KREDIT MASYARAKAT PADA KOPERASI BUNGA BALI - Kadek Ayu Liawathi; Laisa Liza (Jurnal Manajemen, Ekonomi, Keuangan dan Akuntansi, 2023)
The background of this research is how the people of Ungasan Village can get credit, which is one of the programs of the Bunga Bali Cooperative which is located at Jalan Melasti Banjar Kelod Ungasan – South Kuta. Thus, we can find out what the procedures are for granting credit to the cooperative. The research method that the author uses is a qualitative method where information and supporting data are used in collecting data using several methods, namely by using interviews, field studies and literature studies. The results of this study will provide a clear picture of how the procedure for granting credit to the community at the Bunga Bali Cooperative is. Looking at the results of the research, at the end of this study, the authors conclude that the Bunga Bali Cooperative has a very important role in helping support the local community's economy with a very simple credit granting procedure for the community.